Perkembangan Kajian Teoritis Tafsir di Barat dan Pengaruhnya Terhadap Sarjana Muslim - Muhammad Amin (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2019)
This paper aims to examine the development of the study of the Qur’an and interpretation in the West and its influence on Muslim scholars. This paper uses descriptive analysis method. The development of Islamic studies in the West, especially the Islamic holy book, began with the translation of the Qur’an and Arabic literature from the Muslim heritage of Andalusia (Spain). The Western movement in studying the eastern world including the Islamic world was known as the Orientalism movement in the 18th century. Western scientific studies of the Qur’an have become a new trend and interesting object of research to the present. Many works were born by Western researchers who contributed to the development of Qur’anic studies in the Islamic world. Muslim scholars responded to Islamic studies in the West with various responses. Some accept and make it a new scientific discourse in Islam. But not a few also refused because they were told that the study contained certain motives behind it. Apart from the controversy, Islamic studies in the West continue to this day. The works of Western scholars have had a considerable influence on the development of thought in the Islamic world.